Oyapock coopération santé : une collaboration transfrontalière pour une meilleure prise en charge du VIH dans le bassin de l’Oyapock - Collectif (Confins)
This article presents an example of health cooperation between France and Brazil through a project called « Oyapock Coopération Santé » meaning health cooperation along the Oyapock river. It aims to provide patients living with HIV (PlHIV) with a better access to medical care in the frontier area of the Oyapock river. PlHIV living in Oiapoque, the Brazilian border city, face constraints of mobility for accessing to a specialized care in their own state. They also have a positive representation of the French Healthcare system. For these reasons, they prefer to cross the border to seek care in French Guiana. However, this follow-up is not optimal as patients need to pay the trip, deal with the fact they are staying illegally in the French territory and other administrative difficulties.  The purpose of the projet was the creation of a dedicated medical care for PlHIV in Oiapoque so they can have access to a quality follow-up in their territory of residence. Many French and Brazilian stakeholders from different socio-professional backgrounds worked together on this project. They had to learn to work together and to collaborate in a complex intercultural environment facing cultural and linguistic barriers.